Karakteristik Tanah Dan Iklim Sebagai Indikator Hidrologi Di Daerah Aliran Sungai Tamiang Provinsi Aceh - Azizah, Cut; Nuraida, Nuraida; Robo, Sarif (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2022)
quantitative understanding of hydrological behavior watershed can be known from soil and climate characteristics. Soil characteristics were analyzed based on primary data from disturbed soil sampling to determine the soil texture class. The Texture Class was analyzed in the Soil Laboratory Bogor Agricultural Institute and classified by the USDA method. Climate characteristics of watershed Tamiang were analyzed using observational rainfall data and temperature data, to identify rain patterns, climate types, and the influence of ENSO and IOD on the Tamiang watershed. Climatic types are classified by the Schmidt-Ferguson, Oldeman and Koppen methods. The effect of ENSO and IOD on the regional climate of watershed Tamiang was analyzed using the climate explorer tool. As a result of the soil texture analysis, watershed Tamiang is dominated by clay texture. The characteristic rain pattern is equatorial with peak rainy seasons of May and October. The influence of ENSO's global climate on the regional climate of the Tamiang watershed is in the weak category with a correlation of -0.347, while the influence of IOD is very weak with a correlation of 0.089.